FEATURES OF ARTISTIC DECORATION OF MODERN EXHIBITION SALONS OF BAKU CITY: FROM NATIONAL SYMBOLSISM TO HUMAN CULTURAL VALUES (Journal of Pharmaceutical Negative Results, 2023)
The article deals with the artistic and aesthetic principles of the design of modern art galleries, as well as the conditions for demonstrating works of art in them. The authors present the scientific problem in three interrelated directions. These are the problems of decorating an art salon, demonstrating a work of art in certain aesthetic conditions, and the quality of visual perception, which is formed under the influence of the first two factors. As an object of study, the authors chose exhibition salons and art galleries in Baku City, which is one of the major centers of cultural events in the country. The authors state that modern art galleries are located both in the old part of the city and in large contemporary museums and centers, due to the historical conditions of the formation of the city. The latter differs from the galleries in the historical part of the city in larger sizes, however the common principles of interior design, as well as the spirit of the historical past, which imbue the walls and streets of the old city, become an indispensable cultural and historical element of these galleries.